Postprandial lipid profile abnormalities in Type 2 Diabetes Mellitus - Dr Chetan Phadke; Dr Mahajan SN (Medico Research Chronicles, 2019)
Background: Dyslipidemia is commonly seen as diabetes. Type 2 DM is one of the most common secondary causes of hyperlipidemia. Type 2 diabetes mellitus is associated with the development of premature arteriosclerosis and higher cardiovascular morbidity and mortality. Diabetic dyslipidemia is believed to play an important role in the pathogenesis of accelerated atherosclerosis in this condition. The predominant lipid abnormalities seen in diabetes mellitus are an elevated serum triglyceride (Tg) level and a low HDL-C level. While several studies have found a significant association of fasting hypertriglyceridemia and coronary artery disease (CAD) in diabetes mellitus, the relationship is not consistent particularly after adjusting for fasting HDL-C Levels.9 It is being increasingly believed that atherosclerosis is a postprandial phenomenon as at least with respect to lipids, we are in the postprandial phase for nearly 2/3rd of the day. High postprandial triglycerides have shown a strong and independent association with CAD. Earlier studies of postprandial lipids in diabetes mellitus have suggested abnormalities of Tg metabolism secondary to insulin resistance (15) although results have not been consistent.Aims: To assess the postprandial lipid abnormalities in type 2 diabetic patients attending PRH Loni.Objective: To study postprandial lipid profile abnormalities in Type 2 diabetes patients as compared to non diabetics.Methodology: The present study was a prospective case-control type of study that was conducted in Pravara Rural Hospital, Loni. (PRH) with a sample size of 187 (137 cases and 50 controls).Results: The mean age of cases was 57.78 ±12.79 years and of controls was 60.50 ±14.39 years. The fasting bsl in cases was 204.61 ±105.01mg/dl and controls were 98.52±30.03 mg/dl. Postprandial bsl was 235.13 ±114.85 mg/dl in cases and 141.92 ±62.47 mg/dl in controlsPhadke C. & (P= 0.0001; P<0.05 is significant). Total cholesterol level in cases was 157.52 ±53.08 mg/dl and in controls was133.06 ±34.22 (P=0.002). Triglycerides level was 185.23 ±104.34 mg/dl in cases and 123.70 ±47.83 mg/dl in controls (P=0.0001). VLDL value in cases was 37.14 ±21.41mg/dl and in controls was 25.14 ±10.46mg/dl (P=0.0002).